Gambaran Pasien Stroke terhadap Skor NIHSS di Rumah Sakit Daerah Gunung Jati Kota Cirebon - Devinda Salva Krisna Larasati; Dasa Sariadi; Agus Kusnandang (Universitas Pahlawan Tuanku Tambusai, 2026)
Stroke is a neurological emergency that leads to disability and death. NIHSS is used to measure stroke severity, with factors including age, gender, and blod pressure. Aim : To determine the profile of stroke patients based on NIHSS scores at RSD Gunung Jati Kota Cirebon. Methods : This study is a descriptive observational study using medical record data. The sampling technique used was non-probability sampling, specifically purposive sampling . Results : Of the 70 stroke patients at Rumah Sakit Daerah Gunung Jati Kota Cirebon, 72.9% had ischemic stroke, and 27.1% had hemorrhagic stroke. The majority of ischemic stroke patients had grade II hypertension (59.6%), and hemorrhagic stroke patients also predominantly had grade II hypertension (40.4%). Ischemic stroke patients generally had severe NIHSS scores, while hemorrhagic stroke patients tended to have very severe scores. Males dominated both ischemic stroke (68.4%) and hemorrhagic stroke (31.6%). Middle-aged and young adults were the most affected by ischemic stroke, while hemorrhagic stroke was more common in young adults and the elderly. Conclusion : At RSD Gunung Jati Kota Cirebon, the majority of stroke patients experienced ischemic stroke, while the remainder had hemorrhagic stroke. Most ischemic stroke patients had grade II hypertension, and the same was observed in hemorrhagic stroke patients. Ischemic stroke was more often associated with severe NIHSS scores, whereas hemorrhagic stroke was frequently classified as very severe. Males were more dominant in both types of stroke, with ischemic stroke patients mostly in the middle-aged and young categories, while hemorrhagic stroke occurred more frequently in young adults and the elderly.